Writing Practices for Mainstream Teachers of Middle School English Learners: Building on What We Know Works Effectively. Issue 2 (3rd April 2018) - Haas, Eric; Goldman, Julie; Faltis, Christian
Abstract: Improving the writing of middle-school English learners can improve their academic thinking, literacy, and content knowledge. The Writing Reform and Innovation for Teaching Excellence (WRITE) program uses six high-leverage writing practices and develops teacher capacity through professional learning activities anchored in the group grading of common writing assignments. A recent 2-year evaluation of the WRITE program found that it increased middle-school teachers' implementation of best writing practices and also improved English learners' general literacy scores.